The Effect of Ad Content and Ad Length on Consumer Response towards Online Video Advertisement - Djoko Raditya; Willy Gunadi; Dennis Setiono; Jonathan Rawung (Bina Nusantara University, 2020)
The research aimed to determine the moderating effect of advertisement (ad) length on the relationships between ad content and the intention of skipping, as well as ad irritation. The research attempted to fill in the lacuna in the academic literature on the said issue. In doing so, it examined consumers' responses towards the consumers' intention of adskipping and irritation. The experimental research utilized four video ads with varying durations and containing both entertaining and boring content, with long and short ad length. The research sample comprised 120 respondents spend at least more than 1 hour online. The research employed convenience sampling and the method of Univariate Analysis of Variance Linear Model. IBM SPSS Statistics was used for data analysis. The results reveal that the content and length of an online video ad have a direct effect on consumers' ad irritation and intention of skipping. The research concludes that the perceived entertainment of an online video ad significantly affects consumers' intention of skipping and ad irritation. Furthermore, the length of video ads has a major impact on their intention of skipping and ad irritation.